Social co-configuration in online language learning - Sun, Susan Y. H.; Goodyear, Peter (Australasian Journal of Educational Technology, 2020)
University students involved in online courses play an active role in adapting the tasks they are set and the environment(s) in which they work. They also make adjustments to their working relationships with other people in an effort to improve their learning and/or fit study demands into wider life. The term co-configuration refers to the ways in which students customise what has been designed for them. Co-configuration is important but often invisible to the teachers and designers responsible for the courses. In this study, we focused on students’ co-configuration where it has a strong social character. We drew on concepts from realist evaluation and the activity-centred analysis and design framework to examine students’ social co-configuration. Twenty-six online language learning students were interviewed. Two main areas of social co-configuration emerged. Firstly, students co-configured working methods and relationships, roles, and divisions of labour in order to tackle group tasks. Secondly, students purposefully wove learning activity into their wider social environment, creating a social fabric that further enhanced and enriched their learning opportunities. The findings provide insights into students’ social co-configuration. We argue that this is important for educational designers who aim to understand the mechanisms that connect educational designs to learning outcomes.